Operative pediatric surgery - Spitz, Lewis; Coran, Arnold G; Teitelbaum, Daniel H; Tan, Hock Lim; Pierro, Agostino (CRC Press/Taylor & Francis, 2013)
The seventh edition of the acclaimed text Operative Pediatric Surgery continues to provide a unique level of comprehensive detail on the full range of surgically treatable conditions presented in neonate and childhood as well as in utero. With an international list of authors, the chapters have been updated and complemented by the high-quality artwork that has established this operative guide as the standard reference for the pediatric surgeon.
Keywords: chirurgie operační; chirurgie; Child; Infant, Newborn; pediatrie; dítě; novorozenec; Surgical Procedures, Operative